Description of military apparatus in the Śrī-kālacakra-nāma-tantra-rāja - Strelkov, Andrei (Acta Orientalia Vilnensia, 2008)
Russian Academy of Sciences, Institute of Oriental Studies, St. PetersburgIn the Śrī-kālacakra-nāma-tantra-rāja, a Buddhist treatise from the first half of the 11th century, there is a thematic fragment containing a description of military apparatus and their use in battles. In this article, the point of view that we are really dealing with a description of military apparatus and not with a symbolic description of the psychophysical practices of Buddhist yoga is developed. In our point of view, the reason for the subject of war being represented in this Buddhist work should be searched for in the reality of the tragic times in which the text was made―the times of destructive raids made on India by the ruler Mahmud of Ghazni. The article classifies the military apparatus mentioned in the Śrī-kālacakra-nāma-tantra-rāja, describes the basic technical characteristics of these mechanisms, and considers their function. The given subjects are considered with the drawing in the commentary Vimalaprabhā (11th century) and commentaries by Tibetan scholar Buton Rinchen Drub (1290–1364).